2022
DOI: 10.1038/s41419-022-05022-1
|View full text |Cite
|
Sign up to set email alerts
|

Ets1 mediates sorafenib resistance by regulating mitochondrial ROS pathway in hepatocellular carcinoma

Abstract: The incidence and mortality of hepatocellular carcinoma (HCC) are on a rise in the Western countries including US, attributed mostly to late detection. Sorafenib has been the first-line FDA-approved drug for advanced unresectable HCC for almost a decade, but with limited efficacy due to the development of resistance. More recently, several other multi-kinase inhibitors (lenvatinib, cabozantinib, regorafenib), human monoclonal antibody (ramucirumab), and immune checkpoint inhibitors (nivolumab, pembrolizumab) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…It has been shown that the transcription factor E26 transformation–specific-1(Ets-1), which is commonly increased in sorafenib-resistant tumor cells, promotes key EMT gene expression ( Gluck et al, 2019 ). Further studies by Vishnoi et al (2022) identified antioxidant protein GPX2 as a downstream mediator of Ets-1 induced sorafenib resistance, and knockdown of GPX2 expression significantly increased the sensitivity of sorafenib resistant cells to sorafenib ( Vishnoi et al, 2022 ). The results indicate the activation of a novel Ets-1-GPX2 signaling axis in sorafenib resistant cells, targeting which might successfully antagonize resistance ( Vishnoi et al, 2022 ).…”
Section: Acquired Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the transcription factor E26 transformation–specific-1(Ets-1), which is commonly increased in sorafenib-resistant tumor cells, promotes key EMT gene expression ( Gluck et al, 2019 ). Further studies by Vishnoi et al (2022) identified antioxidant protein GPX2 as a downstream mediator of Ets-1 induced sorafenib resistance, and knockdown of GPX2 expression significantly increased the sensitivity of sorafenib resistant cells to sorafenib ( Vishnoi et al, 2022 ). The results indicate the activation of a novel Ets-1-GPX2 signaling axis in sorafenib resistant cells, targeting which might successfully antagonize resistance ( Vishnoi et al, 2022 ).…”
Section: Acquired Drug Resistancementioning
confidence: 99%
“…Further studies by Vishnoi et al (2022) identified antioxidant protein GPX2 as a downstream mediator of Ets-1 induced sorafenib resistance, and knockdown of GPX2 expression significantly increased the sensitivity of sorafenib resistant cells to sorafenib ( Vishnoi et al, 2022 ). The results indicate the activation of a novel Ets-1-GPX2 signaling axis in sorafenib resistant cells, targeting which might successfully antagonize resistance ( Vishnoi et al, 2022 ). Tan et al (2019) found that tumor necrosis factor (TNF-α), a key cellular inflammatory factor, can promote sorafenib resistance in HCC cells by inducing EMT through activating the TNF-α/NF-κB/EMT pathway, and inhibition of TNF-α expression using ulinastatin significantly enhanced the anti-tumor effect of sorafenib in HCC cells with high TNF-α expression.…”
Section: Acquired Drug Resistancementioning
confidence: 99%
“…At present, it is generally believed that unlike NSCLC, mutations in TKIs (such as sorafenib) targets, which include receptor tyrosine kinases (RTKs, such as vascular endothelial growth factor receptor [VEGFR], platelet-derived growth factor [PDGFR], or c-kit or the kinase associated with the mitogen-activated protein kinase/phosphoinositide 3 kinase protein kinase B [MAPK/PI3K-AKT pathway]) in HCC cells are not the main mechanism for the difference in sensitivity or resistance to sorafenib in HCC patients [ 37 , 38 ]. Correspondingly, various mechanisms of HCC cell resistance to sorafenib include several possibilities: (1) Notch, mammalian target of rapamycin [mTOR], and other cell pro-survival, anti-apoptosis-related pathways can lead to up-regulation of cell resistance to TKIs [ 39 ]; (2) the epithelial–mesenchymal transition (EMT) process can reduce the polarity of HCC cells and induce the resistance of HCC cells to sorafenib and other TKIs [ 40 42 ]; (3) HCC-related cancer stem cells and HCC cells are closely associated with sorafenib resistance [ 43 ]; and (4) the mutual compensation between different signaling pathways (such as c-MET can induce resistance to multiple TKIs, including sorafenib) [ 44 ]. Our group has conducted many studies on the resistance of HCC to molecularly targeted drugs and found that the PXR can also be an important mechanism for the resistance of HCC cells to sorafenib [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The production of ROS in a variety of cancers has been proven to be a “double‐edged sword.” Low levels of ROS can promote the survival and metastasis of cancer cells, while excessive ROS accumulation inhibits cancer cells by inducing G2/M cell cycle arrest and apoptosis to inhibit the growth of cells 40,41 . Sorafenib can induce excessive accumulation of ROS in HCC cells, leading to the release of cytochrome C from mitochondria into the cytoplasm, triggering programmed cell death and thereby killing HCC cells 40,42 . ROS scavengers can reduce the killing effect of sorafenib on HCC cells, 43,44 which shows that sorafenib is at least partly dependent on ROS production to kill HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Sorafenib can induce excessive accumulation of ROS in HCC cells, leading to the release of cytochrome C from mitochondria into the cytoplasm, triggering programmed cell death and thereby killing HCC cells. 40,42 ROS scavengers can reduce the killing effect of sorafenib on HCC cells, 43,44 which shows that sorafenib is at least partly dependent on ROS production to kill HCC cells. We found that NFIB could reduce the accumulation of ROS in HCC cells caused by sorafenib.…”
Section: Ta B L Ementioning
confidence: 99%